Effect of Higher Doses of Nitrogen and Phosphate on Unirrigated Wheat - Pathak, S.S. (Journal of Soil and Water Conservation, 2022)
Wheat occupies thc second largest area under cultivated crops in Madhya Pradesh and thus holds an important position in the production of food crops. The total area under the crop in the year 1956-57 was 6287.480 thousand acres out of a total culti- vated area of 37665.622 thousand acres with a total production of 11040 thousand tons, giving an average yield of only 393 lbs per acre for the state which according to any standard is a poor yield—a matter of real concern considering the importance of food crops. A scientific study of the problem points to the deficiency of plant nutrients and moisture availability throughout the crop growing period as the main reasons for this deplorable state of things. In the greater part of the cultivated area the crop depends solely on the rain received during the preceeding Monsoon and very little, if at all, during the growth period and consequently suffers considerably from paucity of moisture. In some areas it is possible to give one to two irrigations to wheat where sources permit. This, however, is extremely limited as only 15.39 per cent of the total area under the crop given above is irrigated. Nitrogen content of the Madhya Pradesh soils is also generally known to be poor though deficiency of phosphates is somewhat localised. This nitrogen deficiency cannot be replenished by the available F.Y.M.